PREACHERS AND HEARERS IN REVOLUTIONARY LONDON: CONTEXTUALISING PARLIAMENTARY FAST SERMONS. (24th October 2014) - Hughes, Ann
ABSTRACT: Studies of preaching in England during the 1640s and 1650 have focused on the high-profile sermons, preached before the parliament on fast days and other special days of thanksgiving, relying in particular on analysis of preachers' texts as published in print. This paper explores ways of placing the fast sermons in broader contexts, drawing on the lively scholarship on early modern sermons that presents them as events as well as texts, dynamic encounters between preachers and hearers. This paper thus explores the responses of conscientious hearers to sermons in London in the 1640s and 1650s, through a variety of notes kept by pious Puritans, broadly sympathetic to the parliament's cause, including the artisan Nehemiah Wallington, John and Katherine Gell from the provincial gentry and John Harper, a city fishmonger. For these hearers, sermon note-taking had enduring purposes, for reflection, meditation and discussion, sometimes across generations; recording the immediate political context or the polemical arguments of the fast sermons was not necessarily their priority. Hearers' notebooks place the fast sermons within a broader context of attendance at more 'routine' pastoral and didactic preaching in London parishes, revealing also that a preacher like Stephen Marshall, best known for his dynamic sermons before the parliament, spent most of his time on less controversial series of sermons on central issues of Protestant faith. Note-taking practices suggest that too sharp a contrast between polemical and routine preaching would be misleading; the fast sermons could be apprehended in a variety of ways by conscientious Puritan hearers, while sermons with a more pastoral focus nonetheless exhibited clear signs of the tensions and dilemmas provoked by the religious conflicts of the period.